Accuracy of wrist-worn heart rate monitors for rate control assessment in atrial fibrillation. (1st February 2020) - Al-Kaisey, Ahmed M.; Koshy, Anoop N.; Ha, Francis J.; Spencer, Ryan; Toner, Liam; Sajeev, Jithin K.; Teh, Andrew W.; Farouque, Omar; Lim, Han S.
Abstract: Background: Wrist-worn heart rate (HR) monitors are increasingly popular. A paucity of data exists on their accuracy in atrial fibrillation (AF) in ambulatory patients. We sought to assess the HR accuracy of two commercially available smart watches [SW] (Fitbit Charge HR [FB] and Apple Watch Series 3 [AW]) compared with Holter monitoring in an ambulant patient cohort. Methods: Thirty-two participants ≥18 years referred for 24-hour Holter monitoring were prospectively recruited. Each participant was randomly allocated to wear either a FB or AW along with their Holter monitor. Results: Across all devices, 53, 288 heart rate values were analysed from 32 participants. Twenty wore the AW (17 had persistent AF and 3 had sinus rhythm [SR]) while 12 participants wore the FB (9 in persistent AF and 3 in SR). Participants in SR demonstrated strong agreement compared to Holter monitoring (bias <1 beat, limits of agreement [LoA] −11 to 11 beats). In AF, both devices underestimated HR measurements (bias −9 beats, LoA −41 to 23). The degree of underestimation was more pronounced when HR > 100 bpm (bias of −28 beats for HR range 100–120 bpm, −48 for 120–140 bpm, and −69 for >140 bpm) compared to a slower HR (bias of −6 for HR range 80–100 bpm, <1 for 60–80 bpm, and −1 for <60 bpm). Conclusion: In ambulatory patients, smartwatches underestimated HR in AF particularly at HR ranges >100 bpm. Further improvements in device technology are needed before integrating them into the clinical management of rate control in AF. Highlights: Wrist-worn heart rate (HR) monitors are increasingly popular. A paucity of data exists on their accuracy in atrial fibrillation (AF) in ambulatory patients. In ambulatory patients, they underestimated HR in persistent AF particularly at ranges >100 bpm. Further improvements in device technology are needed before they can be adopted into the care of AF.